SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI MADRASAH TSANAWIYAH DARUSSALAM PONDOK AREN TANGERANG SELATAN - Yumnah (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2021)
In general, this study aims to determine the implementation of academic supervision of Madrasah principals in improving the professional competence of teachers in M.Ts. Darussalam Pondok Aren Tangerang Selatan and its implications for the learning activities carried out by teachers. This study uses the phenomenology method, namely the study of visible and real phenomena with data collection techniques through interviews, observation and documentation. Meanwhile, the data analysis used qualitative descriptive analysis in the form of descriptions of the results of interviews and observations and complemented with data obtained from supporting documents, such as books on the results of the headmaster's revision and other required documents. The subjects of this study were the principal of the madrasah and the teacher council. The research findings in this study consist of two findings, namely:First, the implementation of academic supervision of Madrasah principals in improving the professional competence of M.Ts. Darussalam Pondok Aren, South Tangerang, is carried out through the stages of planning, implementation, evaluation and follow-up with a focus on coaching: (1) mastery of learning concepts and models that support the subjects it teaches; (2) developing teaching materials that are broad and in-depth which are presented in a creative, innovative and fun way; (3) the use of information and communication technology as a medium of learning and self-development for students; (4) continuous development of teacher professionalism by taking reflective action,Second, the implications of implementing the academic supervision of Madrasah principals on the professional competence of teachers in M.Ts. Darussalam Pondok Aren Tangerang Selatan is an increase in the professional competence of teachers as seen from the improvement and improvement of the quality of learning carried out by the teacher, so that it is more active, innovative, creative, effective and enjoyable for students, so that the learning outcomes of students have also seen an increase. on the average value in the subject that the teacher teaches